2001
DOI: 10.1007/s003300000628
|View full text |Cite
|
Sign up to set email alerts
|

Lesser sac hematoma as a sign of rupture of hepatocellular carcinoma in the caudate lobe

Abstract: The purpose of this study was to evaluate the CT findings of rupture of hepatocellular carcinoma (HCC) in the caudate lobe of the liver. The CT scans of five cases of rupture of HCC in the caudate lobe of the liver were retrospectively reviewed and correlated with clinical records. All cases showed exophytic tumors in the caudate lobe of the liver and high-attenuation hematomas in the lesser sac on CT. A lesser sac hematoma may be a sentinel clot sign of rupture of HCC in the caudate lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The clinical picture was very similar to that of the present case. Hemorrhage due to injury to the caudate lobe often flows into the retroperitoneal cavity rather than into the abdominal cavity, resulting in a retroperitoneal hematoma [ 9 , 10 ]. Therefore, due to the limited space compared to the intraperitoneal, the patient may arrive at the hospital in a stable circulatory state immediately after the injury but may gradually enter shock and become severely ill.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture was very similar to that of the present case. Hemorrhage due to injury to the caudate lobe often flows into the retroperitoneal cavity rather than into the abdominal cavity, resulting in a retroperitoneal hematoma [ 9 , 10 ]. Therefore, due to the limited space compared to the intraperitoneal, the patient may arrive at the hospital in a stable circulatory state immediately after the injury but may gradually enter shock and become severely ill.…”
Section: Discussionmentioning
confidence: 99%
“…When HCC ruptures in the caudate lobe, particularly in the Spiegel lobe, a hematoma is often formed inside the omental bursa (lesser sac) due to its anatomical position [1,3], and, though rare, a case in which a hematoma was formed in the retroperitoneum has also been reported [4]. …”
Section: Discussionmentioning
confidence: 99%
“…The liver is an organ inside the peritoneal cavity, so the rupture of HCC generally causes hemoperitoneum. Among these cases, few reports exist on the rupture of HCC originating from the caudate lobe [1,2] in which a hematoma is often formed in the omental bursa (also known as the lesser sac) [1,3]. On the other hand, hemothorax is a very unusual presentation of ruptured HCC, and is accompanied by high mortality secondary to uncontrollable hemorrhage because the negative pressure inside the pleural cavity makes spontaneous hemostasis difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Iwasaki et al and Lin et al reported cases similar to the present one, in which HCC of the caudate lobe of the liver burst and caused a lesser sac hematoma. 11,12 However, the mechanism of intracavitary hemorrhage caused by the ruptured HCC remains unclear. In the present case, bleeding was detected even in the subcapsule of the right hepatic lobe.…”
Section: Figurementioning
confidence: 99%